Два погляди на «етнонаціональну ситуацію» в Іспанії - Кожановський, О. (Народна творчість та етнографія, 2010)
Статья посвящена вопросу этнонациональной ситуации в Испании. Автор сравнивает два взгляда на национальный вопрос в Испании: первый – тот, который сформировался в советской науке под влиянием доминирующей тогда «теории этноса», другой – испанский взгляд на решение национального вопроса, абсолютно отличающийся от устоявшегося в советской и российской этнологии научной традиции. The article is devoted to the ethnonational situation’s issue in Spain. The author compares two different opinions on the national in Spain: on the one hand, a view that appeared in the circles of the Russian scientists on the problem proceeding from the then dominant «theory of ethnos», and on the other hand, a Spanish look at the national issue’s solution which absolutely differs from the established one in the Soviet and Russian ethnology scientific tradition.